MODIFIKASI KOPOLIMER KARET ALAM SIKLIS GRAFTING ASAM OLEAT MENGGUNAKAN INISIATOR BENZOIL PEROKSIDA DAN BAHAN PENGISI BENTONIT-CETIL TRIMETIL AMONIUM BROMIDA - Ahmad Hafizullah Ritonga; Barita Aritonang; Liver Iman Putra Zai (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2018)
Research on the modification of Cyclic Natural Rubber (CNR) grafting Oleic Acid (OA) copolymer using initiator of Benzoyl Peroxide (BPO) and the filler of bentonite-Cetil Trimethyl Ammonium Bromide (CTAB) has been carried out, which aims to determine the method of modifying Cyclic Natural Rubber (CNR) and Oleic Acid (OA) so it can produce CNR-g-OA copolymer through grafting method with BPO initiator mixed together with bentonite-CTAB. This research was conducted in three stages. The first stage is the process of dissolving CNR using xylene. The second stage is the process of mixing CNR solution and OA with the composition (70:30) phr, followed by the addition of BPO initiator and bentonite-CTAB filler. The third stage is characterization using FTIR and Scanning Electron Microscopy (SEM). The results of the analysis using FT-IR showed an absorption at 1708,23 cm-1 which indicated the presence of C=O bonds from oleic acid which had been grafted on CNR, and increased intensity after addition of bentonite-CTAB at 1568,96 cm-1; 1446,13 cm-1; 1255,66 cm-1; and 866,94 cm-1. Characterization results using SEM showed that the mixing of Bentonite-CTAB in KAS-g-OA was evenly distributed and quite homogeneous.